Investigação de assinaturas de seleção positiva em genes associados à localização do hospedeiro em espécies do grupo repleta de Drosophila - Manfré, Bianca [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The host changes observed in the repleta group of Drosophila, in which the ancestral character state is the use of cacti of the genus Opuntia as hosting and reproduction sites, for the use of chemically more complex columnar cacti in several species, involved the evolution of chemosensory proteins that enable localization and recognition of the host site. Evolutionary processes and the role of positive natural selection in this adaptive process are still poorly explored. Using chemosensory genes of odorant binding proteins (Obps) and odorant receptors (Ors) for representatives of the repleta group, it was possible to identify sites with positive selection signatures in about 84% of the Obp genes and 79% of the Or genes analyzed. Analysis of the location of these sites in the structure of these proteins allowed us to identify patterns of amino acid substitution that probably affected signal transduction at OR receptors and the recognition of odorant molecules by OBPs. The results of this study support the role of positive selection in the evolution of chemosensory genes whose protein products act on host localization in cactophilic species.

As mudanças de hospedeiro observadas no grupo repleta de Drosophila, no qual o estado de caráter ancestral é o uso de cactos do gênero Opuntia como sítios de hospedagem e reprodução, para o uso de cactos colunares quimicamente mais complexos em diversas espécies, envolveu a evolução de proteínas quimiossensoriais que habilitassem a localização e reconhecimento do sítio hospedeiro. Os processos evolutivos e o papel da seleção natural positiva nesse processo adaptativo são ainda pouco explorados. Utilizando genes quimiossensoriais de proteínas de ligação odorante (Obps) e receptores odorantes (Ors) para representantes do grupo repleta, foi possível identificar sítios com assinaturas de seleção positiva em cerca de 84% dos genes Obp e 79% dos genes Or analisados. Análises sobre a localização desses sítios na estrutura dessas proteínas permitiu identificar padrões de substituição de aminoácidos que provavelmente afetaram a transdução do sinal nos receptores ORs e o reconhecimento das moléculas odorantes por OBPs. Os resultados deste estudo suportam o papel da seleção positiva na evolução de genes quimiossensoriais cujos produtos proteicos atuam na localização do hospedeiro em espécies cactofílicas.
Investigation of positive selection signatures in genes associated with host location in species of the Drosophila replete group
Keywords: Cactophilic species; Host change; Odor binding proteins; Odorant receptors; Selection signatures; Espécies cactofílicas; Mudança de hospedeiro; Proteínas de ligação odorante; Receptores odorantes; Assinaturas de seleção